2014
DOI: 10.1246/bcsj.20140261
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecularly Engineered Functional π-Assemblies Based on Complementary Hydrogen-Bonding Interactions

Abstract: As details of exciting photonic and electronic properties arising from self-assembled functional dyes and related π-conjugated molecules become clearer, strategies for control of short and long-range chromophorechromophore orientations, regulation of ππ stacking arrangements, construction of self-organized nano-to-microscale architectures, diversification of materials properties, analysis of self-assembly pathways, and impartment of stimuli-responsive properties, are all becoming important issues in the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(82 citation statements)
references
References 160 publications
2
80
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] In order to achieve these functionalities, highlyordered, adaptive nanostructures formed via a cooperative supramolecular polymerization mechanism are highly desirable. 18 The introduction of orthogonal noncovalent interactions, 19 from which hydrogen bonding and combinations with other secondary interactions are by far the most exploited ones, 20 represents a rational means for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] In order to achieve these functionalities, highlyordered, adaptive nanostructures formed via a cooperative supramolecular polymerization mechanism are highly desirable. 18 The introduction of orthogonal noncovalent interactions, 19 from which hydrogen bonding and combinations with other secondary interactions are by far the most exploited ones, 20 represents a rational means for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…303 These fabrication processes may be linked even with organic synthetic approaches 304,305 and supramolecular organization. 306,307 However, more important efforts for practical usage and industrial applications would be those for mass production, 63,308310 which would be a crucial step for further development of 2D materials. …”
Section: Resultsmentioning
confidence: 99%
“…While there are several strategies for preparing hybrid materials, molecular self-assembly using noncovalent interactions [5][6][7][8][9][10] is considered a simple and efficient approach to the preparation of hybrid materials [11][12][13][14][15][16] . The nanoscale and mesoscale ordering of the building blocks in these hybrid materials and the resultant morphological features determine their functional properties, which can be modified by exploiting the reversible and adaptive nature of noncovalent interactions 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…16b) 87 . Absorption and fluorescence studies showed that the aqueous dispersion of 40/SWNTs exclusively contained small-diameter nanotubes such as (6, 5: d = 0.757 nm) and (8,3: d = 0.782 nm), whereas the large diameter ones ( (7,5), (8,4), and (7, 6); d = 0.829, 0.840, and 0.895 nm) were removed from the assynthesized SWNTs samples by centrifugation. The rotation around the -C≡C-bonds of the phenyleneethynylene unit of 40 played a crucial role in the helical wrapping of SWNTs having a definite chirality.…”
mentioning
confidence: 99%